A novel plasmid-encoded serotype conversion mechanism through addition of phosphoethanolamine to the O-antigen of Shigella flexneri. - Qiangzheng Sun; Yuriy A Knirel; Ruiting Lan; Jianping Wang; Sof'ya N Senchenkova; Dong Jin; Alexander S Shashkov; Shengli Xia; Andrei V Perepelov; Qiang Chen; Yan Wang; Haiyin Wang; et al. (PLoS ONE, 2012)
Shigella flexneri is the major pathogen causing bacillary dysentery in developing countries. S. flexneri is divided into at least 16 serotypes based on the combination of antigenic determinants present in the O-antigen. All the serotypes (except for serotype 6) share a basic O-unit containing one N-acetyl-d-glucosamine and three l-rhamnose residues, whereas differences between the serotypes are conferred by phage-encoded glucosylation and/or O-acetylation. Serotype Xv is a newly emerged and the most prevalent serotype in China, which can agglutinate with both MASF IV-1 and 7,8 monoclonal antibodies. The factor responsible for the presence of MASF IV-1 (E1037) epitope has not yet been identified. In this study, we analyzed the LPS structure of serotype Xv strains and found that the MASF IV-1 positive phenotype depends on an O-antigen modification with a phosphoethanolamine (PEtN) group attached at position 3 of one of the rhamnose residues. A plasmid carried gene, lpt-O (LPS phosphoethanolamine transferase for O-antigen), mediates the addition of PEtN for serotype Xv and other MASF IV-1 positive strains. These findings reveal a novel serotype conversion mechanism in S. flexneri and show the necessity of further extension of the serotype classification scheme recognizing the MASF IV-1 positive strains as distinctive subtypes.